2014
DOI: 10.1161/hypertensionaha.114.04374
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Hypoxia Leads to Increased Muscle Sympathetic Nerve Activity, Sympathetic Hyperinnervation, Premature Blunting of Neuropeptide Y Signaling, and Hypertension in Adult Life

Abstract: Abstract-Adverse conditions prenatally increase the risk of cardiovascular disease, including hypertension. Chronic hypoxia in utero (CHU) causes endothelial dysfunction, but whether sympathetic vasoconstrictor nerve functioning is altered is unknown. We, therefore, compared in male CHU and control (N) rats muscle sympathetic nerve activity, vascular sympathetic innervation density, and mechanisms of sympathetic vasoconstriction. In young (Y)-CHU and Y-N rats (≈3 months), baseline arterial blood pressure was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 46 publications
1
38
1
Order By: Relevance
“…Blood pressure was not elevated at this age, but blood pressure was increased by 9 months of age in male offspring exposed to prenatal hypoxia relative to male control (23) suggesting that exposure to hypoxia during fetal life programs an increase in basal muscle SNA that precedes the development of increased blood pressure. Despite the increase in sympathetic nerve density, vasoconstrictor responses to sympathetic nerve stimulation were blunted in male prenatal hypoxia offspring at 3 months of age relative to age-matched control counterparts (23). Blockade of the neurotransmitter neuropeptide Y attenuated these responses in male control offspring at 3 months of age with no effect on vasoconstrictor responses to sympathetic nerve stimulation in prenatal hypoxia counterparts (23).…”
Section: The Sympathetic Nervous System and The Developmental Programmentioning
confidence: 80%
See 3 more Smart Citations
“…Blood pressure was not elevated at this age, but blood pressure was increased by 9 months of age in male offspring exposed to prenatal hypoxia relative to male control (23) suggesting that exposure to hypoxia during fetal life programs an increase in basal muscle SNA that precedes the development of increased blood pressure. Despite the increase in sympathetic nerve density, vasoconstrictor responses to sympathetic nerve stimulation were blunted in male prenatal hypoxia offspring at 3 months of age relative to age-matched control counterparts (23). Blockade of the neurotransmitter neuropeptide Y attenuated these responses in male control offspring at 3 months of age with no effect on vasoconstrictor responses to sympathetic nerve stimulation in prenatal hypoxia counterparts (23).…”
Section: The Sympathetic Nervous System and The Developmental Programmentioning
confidence: 80%
“…This study published in Hypertension reported that frequency of single unit muscle SNA and sympathetic innervation of the tibial arteries were increased at 3 months of age in male offspring exposed to prenatal hypoxia (23). Blood pressure was not elevated at this age, but blood pressure was increased by 9 months of age in male offspring exposed to prenatal hypoxia relative to male control (23) suggesting that exposure to hypoxia during fetal life programs an increase in basal muscle SNA that precedes the development of increased blood pressure. Despite the increase in sympathetic nerve density, vasoconstrictor responses to sympathetic nerve stimulation were blunted in male prenatal hypoxia offspring at 3 months of age relative to age-matched control counterparts (23).…”
Section: The Sympathetic Nervous System and The Developmental Programmentioning
confidence: 97%
See 2 more Smart Citations
“…Previous reports suggested that elevated systemic levels of NPY in PE reflect SNS hyperactivity resulting in the long-lasting vasoconstriction and hypertension found in this condition. Such SNS overactivity can be triggered by uterine blood flow restriction, as hypoxia is a strong SNS activator (Rook et al , 2014). However, there are also epidemiological data indicating associations of psychosocial stress in pregnancy with increased risk of preeclampsia, suggesting that the elevated NPY levels observed specifically in MTPE may reflect maternal chronic stress (Klonoff-Cohen et al , 1996; Kurki et al , 2000; Paarlberg et al , 1995; Salvador-Moysen et al , 2012; Sandman et al , 1997; Wadhwa et al , 1996).…”
Section: Discussionmentioning
confidence: 99%